Association Between The Level of Habit of Playing Online Games and Social Behavior In Adolescents - Leling, Apliana Kodu; Trishinta, Sirli Mardianna; Parnawati, Tantry Ajeng (Universitas Tribhuwana Tunggadewi, 2024)
The increasing prevalence of habit of playing online games among adolescents has raised concerns about its potential impact on their social behavior. The purpose of this study was to determine the connection between the level of habit of playing online games and social behavior in adolescents at SMK N 1 Loli. Employing a cross-sectional research design, the population consisted of 50 teenagers, with a purposive sampling technique yielding a sample of 34 teenagers. The study designated habit of playing online games as the independent variable and social behavior as the dependent variable. Data collection involved online game habit questionnaires and social behavior questionnaires, while data analysis employed Fisher's exact test. The finding revealed that most of the respondents have high online game habits (55.9%) and similarly, a significant proportion demonstrated high levels of social behavior (67.6%) The analysis found a statistically significant relationship between the level of online game habits and social behavior in Adolescents at SMK N 1 Loli with a value (P-value = 0.000). To broaden the scope of understanding, future research can consider additional factors that potentially influence both habit of playing online games and social behavior that remained unexplored within this study.